Augmented Reality (AR) and Virtual Reality (VR) Technology in Education: Media of Teaching and Learning: A Review - Tira Nur Fitria (Institut Teknologi Bisnis AAS Indonesia, 2023)
Augmented Reality (AR) and Virtual Reality (VR) are the latest technologies that provide a new color to the field of education. This study reviews the use of AR and VR in education, especially in the teaching and learning process. This study is library research. The analysis shows that AR and VR are the solutions for teachers and students as a medium in the teaching and learning process. AR embellishes existing reality with image elements, sound effects, or text. While, VR creates a new simulation environment that presents a specific topic to students in an engaging, interactive, and experiential way. Several subjects using AR technology in education are: 1) anatomy of living things in Biology, 2) atoms in Chemistry, 3) earth and space in Geography, 4) movie Screening in Film and Television, 5) Computer network topology in Informatics, 6) geometry in Mathematics, and 7) 3D Stories in History. Several subjects which use VR technology in education are: 1) digestive system in Biology, 2) geometry in Mathematics, 3) earth's surface in Geography, 4) artifacts and temples in History, 5) space in Astronomy, 6) surgical operation practicum in Medical, and 7) pilot training in Aviation education. However, AR and VR have benefits and limitations. There are several barriers to implementing AR and VR in educational institutions and some considerations in implementing AR and VR technology in educational institutions. It is hoped that AR and VR can be used as a breakthrough in education and a solution to improving the quality of education in the future.